BET 2: Core stability versus conventional exercise for treating non-specific low back pain. Issue 2 (22nd January 2016) - Davin, John; Callaghan, Michael
Abstract : A short cut review was carried out to establish whether core stability exercises are better than conventional exercise for treating non-specific low back pain. 6 papers were found of which 4 presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. The clinical bottom line is the perception that a core stability rehabilitation programme will improve low back pain has not been proven.